2020
DOI: 10.1016/j.infbeh.2020.101466
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of attention sharing: Orienting and responding to attention in term and preterm 5-month-old infants

Abstract: Highlights Investigated attention in full-term and preterm 5-month-olds and their mothers. Compared attention to persons and objects. Evaluated role of maturity in orienting and responding to attention. Infant attention to persons versus objects was related to maturity. Infant and maternal responsiveness were related to maturity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(31 citation statements)
references
References 67 publications
1
30
0
Order By: Relevance
“…Trained researchers coded parenting behaviours from parent-infant interactions in two stages using Mangold Interact software (Mangold, Software & Consulting, 2000 ). In the first stage, researchers exhaustively coded each interaction for encouragement of infant attention to the caregiver (social), encouragement of infant attention to toys or other objects in the room (objects), and no encouragement of attention (none; Bornstein et al, 2001 , 1991 ; Cote & Bornstein, 2000 ; Gattis et al, 2020 ). This coding stage allowed us to identify all encouragement of attention events (referred to as attention-directing events in Landry et al, 1996 ) and additionally to distinguish between events according to focus of attention so that we could evaluate social- versus object-focused events separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trained researchers coded parenting behaviours from parent-infant interactions in two stages using Mangold Interact software (Mangold, Software & Consulting, 2000 ). In the first stage, researchers exhaustively coded each interaction for encouragement of infant attention to the caregiver (social), encouragement of infant attention to toys or other objects in the room (objects), and no encouragement of attention (none; Bornstein et al, 2001 , 1991 ; Cote & Bornstein, 2000 ; Gattis et al, 2020 ). This coding stage allowed us to identify all encouragement of attention events (referred to as attention-directing events in Landry et al, 1996 ) and additionally to distinguish between events according to focus of attention so that we could evaluate social- versus object-focused events separately.…”
Section: Methodsmentioning
confidence: 99%
“…To capture the context, timing, and appropriateness of parenting behaviours we chose a micro-coding approach that drew on two established observational coding systems (Bornstein et al, 1991 ; Landry et al, 1996 ). We first identified all episodes in which a parent encouraged infant attention to herself or to an object (Bornstein et al, 2001 , 1991 ; Cote & Bornstein, 2000 ; Gattis et al, 2020 ). We then assigned each event, or parenting behaviour, to one of three categories: maintaining, introducing, or redirecting attention (Landry et al, 1996 ).…”
Section: Parenting Beliefs and Behavioursmentioning
confidence: 99%
“…A clear account of when and how preterm birth influences attention needs to consider evidence from naturalistic as well as experimental measures. Gattis et al (2020) evaluated orienting and responding to attention in preterm and term infants during naturalistic interactions with their mothers. To control for extrauterine experience, Gattis et al (2020) matched preterm and term infants on chronological age: all infants were observed 5 months after they were born.…”
Section: Visual Attention In Preterm Infantsmentioning
confidence: 99%
“…MZ birth is a problematic event that disrupts the establishment of parental mental representations and is a potential risk factor not only for child development but also for the construction of parental functioning and a positive mother–child relationship [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. In addition, MZ birth is generally associated with high levels of maternal stress, anxiety and depression, as well as feelings of inadequacy [ 23 , 24 ], ([ 25 ] pp. 61–68), [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%